Product Completion Time Reviewed by Production Costs and Production Capacity in Small Furniture Businesses - Nurfadillah; Rum, Muh.; Rustam, Andi (Borong Newinera Publisher, 2026)
This study aims to analyze the relationship between product completion time and production costs and production capacity in Small and Medium Enterprises (SMEs) furniture in Tellulimpoe District, Sinjai Regency. The background of this study is based on the problem of delays in product completion that impact the income and competitiveness of furniture SMEs. The approach used is descriptive qualitative with the Job Order Costing method as an analytical tool, as well as triangulation techniques in data collection through interviews, questionnaires, and documentation. The results of the study indicate that the efficiency of completion time is greatly influenced by the management of production costs and available capacity. High production costs, lack of equipment, and limited labor cause longer processing times. In addition, low cost capacity also hampers the production process due to limited raw materials and supporting equipment. This study is expected to be a reference in strategic decision-making for furniture SMEs to increase productivity and business competitiveness.